The Distribution Pattern and Population of Blackbuck Antilope cervicapra Linnaeus in Bidar, Karnataka - Asif, Mohammed; Modse, Sanjeeva Reddy (Indian Forester, 2016)
Blackbuck is one of the Antelope species, once widespread across the Indian subcontinent now has become near threatened species. There are no reports of Blackbuck existence in Bidar district in the past hence, the study was conducted to record the distribution and population of Blackbuck in Bidar district for a period of two years from June, 2012 to May, 2014. There are 886 Blackbuck recorded in the district. It is the second highest number in Karnataka next to Ranebennur Blackbuck Sanctuary. In Bidar district, the Bidar taluka witnessed highest population of 503 Blackbuck followed by Aurad (155), Bhalki (120), Basavakalyan (67) and Humnabad (41). The combination of grassland and forest patches with agricultural fields is the ideal habitat for Blackbuck.